PELATIHAN BAHASA INGGRIS BAGI PELAJAR SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS - Fergi Diarta; Septin Bilkhis Silviana; Ayu Pipih Lestari; Elma Aviani; Ranny Rahmawati (LPPM Universitas Bina Bangsa, 2023)
English speaking training is a program designed to enhance the English speaking proficiency of the general public. The training focuses on themes that are relevant to daily activities, such as Daily Activity I, Daily Activity II, Talking About Your Hobbies, and Misconception English Language Education Paradigm in Indonesia. This program is deemed necessary to aid individuals in improving their English speaking abilities. The program is executed in several stages, commencing with the preparation stage, which encompasses scheduling, curating thematic material, participant recruitment, speaker outreach, and Microsoft Teams preparation. Subsequently, the implementation phase of the program ensues, featuring the delivery of thematic content and a discussion between participants and speakers, during which the former are encouraged to address any areas of the material that remain unclear